Kepemimpinan Berkelanjutan : Kepuasan Kerja dan Kinerja Karyawan UMKM Kopi Gerobak Dijakarta - Untung La Paudi (Universitas 45 Surabaya, 2024)
This research focuses on discussing sustainable leadership variables and their influence on employee performance and job satisfaction. The sample used in this study totalled 79 respondents. Data collection techniques from respondents using questionnaires to minimise differences in interpretation between respondents and researchers. The results showed that based on the Thitung value, the sustainable leadership variable is smaller than the Ttable, which is 6.826. and the significance value is smaller than alpha, which is 0.00 <0.05. This shows that sustainable leadership has a positive and significant effect on the job satisfaction variable (Y), it is known that the significance value of job satisfaction is 0.187 <0.05, so it concludes that the job satisfaction variable has no significant effect on employee performance.